Dampak Pajak Karbon terhadap Laporan Keuangan dan Strategi Bisnis Perusahaan Manufaktur : (Studi Kasus Pada Perusahaan PT Mustika Ratu TBK) - Bunga Syalaisha Putri; Elizabeth Tiur Manurung (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study aims to analyze the impact of carbon tax implementation on the financial statements and business strategies of PT Mustika Ratu Tbk, a primary consumer goods company listed on the Indonesia Stock Exchange. The data used is secondary data obtained from the company's 2022 annual report and sustainability report. The research method used is a descriptive quantitative approach, by calculating the amount of carbon tax and analyzing its implications for the company's financial performance and sustainability strategy. The results show that the company's energy consumption in 2022 reached 1,077,438.6 kWh, with total carbon emissions of 991.24 tons of CO2. Based on a carbon tax rate of IDR 30,000 per ton of CO2, the total carbon tax payable by the company is IDR 29,737,305.36 or around 0.044% of the company's net profit, so the impact on the financial statements is still relatively small. This study confirms that carbon tax is not only an additional burden, but also an opportunity for companies to strengthen their competitiveness, support the transition to sustainable business, and reinforce their image as entities that are responsible for the environment.